Investigation of transcriptional dynamics in the Caenorhabditis elegans intestine gene regulatory network - Williams, Robert Thomas Patton, author; Osborne Nishimura, Erin, advisor; Wilusz, Carol, committee member; Hansen, Jeffrey, committee member; Santangelo, Tom, committee member (Colorado State University. Libraries, 2022)
ELT-2 is the major transcription factor required for the activation of Caenorhabditis elegans intestinal development. ELT-2 expression initiates in embryos to promote development and persists after hatching through larval and adult stages. Though the sites of ELT-2 binding have been defined and the transcriptional changes that result from ELT-2 depletion described, the intestine-specific transcriptome profile over developmental time has not been characterized, in part because of the difficulty in isolating intestine from other tissues. To address this knowledge gap, we used Fluorescence Activated Cell Sorting (FACS) to enrich intestine cells and performed RNA-seq analysis at distinct developmental stages. By linking the transcriptome profiles to previous ELT-2 studies, we were able to gain new insight into the role of ELT-2 in the intestinal regulatory network throughout development. Correlation of ELT-2 binding to the intestine transcriptome data, revealed that only 33% of intestine-enriched genes were direct targets of ELT-2 binding in embryos, but that number increased to 75% by the L3 stage. This suggests additional transcription factors may promote intestine-specific transcription early in development. Consistent with this possibility, half of the ELT-2 direct target genes were not transcriptionally dependent on ELT-2 for appropriate expression (i.e. their expression was not impacted following ELT-2 depletion) implying that other factors may compensate in the absence of ELT-2. Among direct target genes that were affected by ELT-2 depletion, equal proportions were over and under-expressed thus ELT-2 can both activate and repress direct target genes. Both activated and repressed sets of ELT-2 target genes were enriched for defense response genes reinforcing recent findings demonstrating ELT-2 participating in mediating the immune response upon pathogen exposure. Fluorescent reporter assays demonstrated that expression of two direct targets of ELT-2 cebp-1 and ets-4 are indeed repressed by ELT-2. Moreover, we observed that ELT-2 repressed its own promoter in a negative feedback loop that regulates elt-2 gene expression. Together, our findings illustrate that ELT-2 contributes directly to roughly 20 – 50% of intestine-specific gene expression, that ELT-2 exerts both positive and negative regulatory control on its direct targets, and that our overall picture of the intestinal regulatory network is incomplete with more intestine specific transcription factors and mechanisms remaining to be discovered.